2019
DOI: 10.3390/mi10080527
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Generation of Amino-Functionalized Hydrogel Microbeads Capable of On-Bead Bioassay

Abstract: Microfluidic generation of hydrogel microbeads is a highly efficient and reproducible approach to create various functional hydrogel beads. Here, we report a method to prepare crosslinked amino-functionalized polyethylene glycol (PEG) microbeads using a microfluidic channel. The microbeads generated from a microfluidic device were evaluated by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS) and confocal laser scanning microscopy, respectively. We found that the microbeads were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…They are inherently non-adhesive to cells and unless modified they are non-biodegradable. Functionalization with molecules such as Arg-Gly-Asp (RGD) motifs (Sionkowska, 2011;Kim et al, 2019), or mixing of natural and synthetic polymers (Krutkramelis et al, 2016), is therefore required for many cellular applications. Alterations of these polymers can be used to provide useful cross-linking approaches such as photopolymerization as demonstrated in PEG (Young et al, 2013;Xia et al, 2017) and PVA (Zhao et al, 2010).…”
Section: Synthetic Hydrogelsmentioning
confidence: 99%
“…They are inherently non-adhesive to cells and unless modified they are non-biodegradable. Functionalization with molecules such as Arg-Gly-Asp (RGD) motifs (Sionkowska, 2011;Kim et al, 2019), or mixing of natural and synthetic polymers (Krutkramelis et al, 2016), is therefore required for many cellular applications. Alterations of these polymers can be used to provide useful cross-linking approaches such as photopolymerization as demonstrated in PEG (Young et al, 2013;Xia et al, 2017) and PVA (Zhao et al, 2010).…”
Section: Synthetic Hydrogelsmentioning
confidence: 99%
“…Two major advantages of hydrogels are that they provide relevant mechanical cues and allow for cell adherence ( Huang et al, 2017 ; Mohamed et al, 2019 ). Commonly used in droplet microfluidics are the natural occurring alginate-based ( Leong et al, 2016 ; Huang et al, 2017 ; Mao et al, 2019 ) or synthetic polyethylene glycol-based (PEG) ( Krutkramelis et al, 2016 ; Kim et al, 2019 ) hydrogels which are primarily gelated using chemical or physical crosslinking. Although these techniques are well developed and understood addition of gelation agents has the potential to negatively affect cell phenotype and viability.…”
Section: Introductionmentioning
confidence: 99%
“…Nasser et al [4] demonstrated a PMMA-based microfluidics device for cost-effective PCR applications. Kim et al [5] made homogenous amino-functionalized hydrogel microbeads for on-bead bioassay.…”
mentioning
confidence: 99%